Epidemiological characteristics of human psittacosis in Guangdong Province, China, 2019–2024 - Zhuang, Yali; Wang, Yu; Zhang, Shujun; Li, Chengcong; Hu, Ting; Zhang, Chenghuan; Huang, Zenglong; Zeng, Qiuhong; Liu, Ze; Weng, Canhui; Luo, Lixian; Zou, Mingqi; et al. (Frontiers in Public Health, 2025)
BackgroundPsittacosis is a non-statutory infectious disease and receives relatively low attention in China. Since 2019, the incidence of psittacosis in Guangdong Province has been continuously increasing. Therefore, it is necessary to understand the epidemiological characteristics, providing a basis for optimizing psittacosis prevention and control.MethodsThis study included psittacosis cases reported in Guangdong Province from 2019 to 2024. Data were collected and a retrospective survey was conducted. The spatiotemporal distribution, clinical manifestations and epidemiological exposure histories were analyzed. Logistic regression model was used to explored the risk factors for psittacosis pneumonia.ResultsA total of 435 psittacosis cases were reported in Guangdong Province. It demonstrated an overall increasing trend in the incidence rate, with cases predominantly occurring in winter and spring. Nansha District in Guangzhou (p < 0.001), Boluo in Huizhou (p < 0.001) and Shunde in Foshan (p = 0.001) were identified as hotspots for psittacosis. The incidence rate of psittacosis was higher in males (χ2 = 17.26, p < 0.001) and in the 50–79 age group (χ2 = 123.45, p < 0.001). Univariate regression analysis showed that underlying diseases are a risk factor for psittacosis pneumonia [OR (95% CI) = 2.47(1.42, 3.31), p = 0.01]. There were 162 cases with a history of epidemiological exposure, but only 42 cases (25.93%) used protective measures.ConclusionThe incidence of psittacosis has been increasing in Guangdong Province recently, posing a threat to individuals with poultry exposure. In the future, it is suggested to enhance the monitoring of individuals with daily contact with poultry, particularly for the older adult, in winter and spring.